2019
DOI: 10.1017/s0007114519002927
|View full text |Cite
|
Sign up to set email alerts
|

The glycation level of milk protein strongly modulates post-prandial lysine availability in humans

Abstract: Industrial heat treatment of milk results in protein glycation. A high protein glycation level has been suggested to compromise the post-prandial rise in plasma amino acid availability following protein ingestion. In the present study, we assessed the impact of glycation level of milk protein on post-prandial plasma amino acid responses in humans. Fifteen healthy, young men (age 26 (SEM 1) years, BMI 24 (SEM 1) kg/m2) participated in this randomised cross-over study and ingested milk protein powder with protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…During thermal processing, chemical reactions between reducing sugars and lysine lead to formation of Maillard reaction products. Such reactivity reduces the availability of lysine (Nyakayiru et al., 2020), hence the FAO recommendation for the use of digestible reactive lysine instead of total digestible lysine to determine the DIAAS. Such considerations will greatly affect the DIAAS value of protein, and possibly its limiting AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During thermal processing, chemical reactions between reducing sugars and lysine lead to formation of Maillard reaction products. Such reactivity reduces the availability of lysine (Nyakayiru et al., 2020), hence the FAO recommendation for the use of digestible reactive lysine instead of total digestible lysine to determine the DIAAS. Such considerations will greatly affect the DIAAS value of protein, and possibly its limiting AA.…”
Section: Discussionmentioning
confidence: 99%
“…During thermal processing, chemical reactions between reducing sugars and lysine lead to formation of Maillard reaction products. Such reactivity reduces the availability of lysine (Nyakayiru et al, 2020), hence the FAO recom-…”
Section: Seeking Nutritional Efficiencymentioning
confidence: 99%
“…Our data clearly demonstrate that food processing of protein ingredients can strongly modulate the post-prandial amino acid response to protein ingestion, even when micellar casein is used as the original protein source. Various forms of processing, such as heating, separation, added salts, cross-linking, drying, and glycation may all modulate the functional properties of dietary protein [43,44]. Furthermore, some of these processes may even occur during the storage of protein [40,41].…”
Section: Plasma Metabolites Micellar Casein Calcium Caseinate Cross-lmentioning
confidence: 99%
“…A recent human trial administering milk protein to healthy young men, which was glycated to different extents, found a reduced lysine availability that was dose-dependent on the level of glycation. This reduced availability was only seen for lysine, not for the other amino acids [ 30 ]. Additionally, Joubran et al (2017) found that the MR changes the functionality of the whey protein α-lactalbumin.…”
Section: Dietary Ages In the Gastro-intestinal Tract: Digestion Amentioning
confidence: 99%